Effects of MS bacteriophages, ultraviolet light, and organic acid applications on beef trim contaminated with STEC O157:H7 and the "Big Six" serotypes after a simulated High Event Period Scenario. (June 2022) - Shebs, E.L.; Giotto, F.M.; de Mello, A.S.
Abstract: A high event period (HEP) occurs when beef processing facilities experience an elevated rate of STEC positive trim samples. In order to avoid contaminated vacuum-packaged beef entering into commerce, primals and subprimals associated to positive trim must be treated with antimicrobials, repackaged, and retested for STEC to ensure product wholesomeness. In this study, we evaluated the efficacy of Bacteriophages (P), Peroxiacetic Acid (PAA), Acidified Sodium Chlorite (ASC), and Ultraviolet light (UV) to reduce the O157:H7 and the Big Six STEC in beef after a simulated HEP scenario. In vacuum conditions and under aerobic conditions, phage applications and a combination of P + UV led to the greatest STEC reduction, respectively ( P < 0.001). Overall, treatments including bacteriophage provided best reductions when compared to non-phage treatments ( P < 0.001, for both vacuum and aerobic conditions). Bacteriophage solutions provided improved control of STEC O157:H7 and the Big Six serotypes when reworking beef after a simulated HEP scenario.